Cost-effectiveness of non-vitamin K antagonist oral anticoagulants for stroke prevention in patients with atrial fibrillation at high risk of bleeding and normal kidney function. Issue 150 (February 2017) - Hernandez, Inmaculada; Smith, Kenneth J.; Zhang, Yuting
Abstract: Introduction: The comparative cost-effectiveness of all oral anticoagulants approved up to date has not been evaluated from the US perspective. The objective of this study was to compare the cost-effectiveness of edoxaban 60 mg, apixaban 5 mg, dabigatran 150 mg, dabigatran 110 mg, rivaroxaban 20 mg and warfarin in stroke prevention in atrial fibrillation patients at high-risk of bleeding (defined as HAS-BLED score ≥ 3). Materials and methods: We constructed a Markov state-transition model to evaluate lifetime costs and quality-adjusted life years (QALYs) with each of the six treatments from the perspective of US third-party payers. Probabilities of clinical events were obtained from the RE-LY, ROCKET-AF, ARISTOTLE and ENGAGE AF-TIMI trials; costs were derived from the Healthcare Cost and Utilization Project, and other studies. Because edoxaban is only indicated in patients with creatinine clearance ≤ 95 ml/min, we re-ran our analyses after excluding edoxaban from the analysis. Results: Treatment with edoxaban 60 mg cost 77, 565/QALY gained compared to warfarin, and apixaban 5 mg cost 108, 631/QALY gained compared to edoxaban 60 mg. When edoxaban was not included in the analysis, treatment with apixaban 5 mg cost 84, 128/QALY gained, compared to warfarin. Dabigatran 150 mg, dabigatran 110 mg and rivaroxaban 20 mg were dominated strategies. Conclusions: For patients with creatinine clearance between 50 and 95 ml/min, apixaban 5 mg was the most cost-effective treatment for willingness-to-pay thresholds (WTP) above 115, 000/QALY gained, and edoxaban 60 mg was cost-effective when the WTP was between 75, 000 and 115, 000/QALY gained. For patients with creatinine clearance > 95 ml/min, apixaban 5 mg was the most cost-effective treatment for WTP thresholds above 80, 000/QALY gained. Highlights: We compared the cost-effectiveness of NOACs and warfarin from the US perspective. We modeled a cohort of atrial fibrillation patients at high-risk of bleeding. For CrCl between 50 and 95 ml/min, edoxaban was most cost-effective. Apixaban would be cost-effective if its price was reduced by 1.3%. For CrCl > 95 ml/min, apixaban was the most cost-effective treatment.